PENINGKATAN KESEHATAN TERNAK UNTUK KESEJAHTERAAN MASYARAKAT DI DESA LINAMNUTU, KECAMATAN AMANUBAN SELATAN, KABUPATEN TIMOR TENGAH SELATAN - Tophianong, Tarsisius Considus; Simarmata, Yohanes Timbun Raja Mangihut Ronael; Utami, Tri (Jurnal Media Tropika, 2022)
Improving livestock health is an important aspect of conserving and fulfillment the nutritional needs of animal sources. Healthy livestock are able to achieve maximum productivity. The purpose of this service was to provide education to farmer and animal health services in local villages. This activity was carried out on January 28-30, 2022 in Linamnutu Village, South Amanuban District, South Central Timor Regency. The method of implementing this service activity includes: (1) counseling on livestock maintenance management to farmers, (2) livestock health services such as physical examination, administered vitamins and medication, (3) distributed chicken eggs to students at SD Negeri Linamnutu. The results of the activity showed that there was an increase in knowledge and awareness of farmers in implementing good management of livestock maintenance, so that livestock become healthy and productive, as well as fulfill of nutrition for the community, especially for children in their growing period.